Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1007/bf03012394
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance and recovery characteristics after sevoflurane or propofol during ambulatory surgery in children with epidural blockade

Abstract: Mark Levine MB FRCPCPurpose: To compare the maintenance and recovery characteristics after sevoflurane with those after propofol in children with epidural blockade. Methods: F~cy unpremedicated, children ASA I-II, 2 -8 yr of age, scheduled for elective urological surgery as outpatients, were randomly allocated to receive either: I) sevoflurane for induction and maintenance of anaesthesia or 2) propofol for induction (2-3 mgkg -~ iv) and for maintenance (5-I0 mg-kg -t-hr -l iv). All children received N20 70% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Significantly higher subjective and observational pain scores in children receiving sevoflurane have been reported in numerous studies. This has been observed in children who have had regional block (2,3,20,21) and in those who have undergone noninvasive procedures (12). This may reflect the effect of severe agitation on scoring pain on a behaviour pain scale.…”
Section: Discussionmentioning
confidence: 96%
“…Significantly higher subjective and observational pain scores in children receiving sevoflurane have been reported in numerous studies. This has been observed in children who have had regional block (2,3,20,21) and in those who have undergone noninvasive procedures (12). This may reflect the effect of severe agitation on scoring pain on a behaviour pain scale.…”
Section: Discussionmentioning
confidence: 96%
“…Data from 2 small studies (1 published only as an abstract) indicate similar times to recovery from anaesthesia for sevoflurane compared with intravenous propofol in children undergoing tonsillectomy [78] or urological surgery [77] (table III) [quantitative data on induction were not reported]. …”
Section: Sevoflurane Versus Propofolmentioning
confidence: 96%
“…In the study by Guard et al, 11 when comparing the sevoflurane group (both for induction and maintenance) and propofol group (induction and maintenance), no significant difference in coughing was found (RR 0.92, 95% CI 0.50‐1.67). Laryngospasm occurred twice in the sevoflurane group but did not occur in the propofol group; therefore, the relative risk could not be calculated.…”
Section: Resultsmentioning
confidence: 92%
“…The study results are outlined in Table 3. Two studies showed no significant difference in hemodynamic or respiratory adverse events 9,11 . Hasani et al 9 showed no difference between groups in coughing, hypotension, bradycardia, and laryngospasm.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation